80 To Transfuse or Not to Transfuse: Choosing blood transfusions wisely in young children hospitalized with iron deficiency anemia. (21st October 2022) - Sun, Dou Lin (Rose); Puran, Allan; Nuaimi, Mohammed Al; AlRiyami, Layla; Kinlin, Laura; Borkhoff, Cory; Kirby, Melanie-Ann; Parkin, Patricia
Abstract: Background: Nutritional iron deficiency anemia (IDA) peaks in prevalence at 6to 36 months of age. Children with severe IDA often present to emergency departments and may be hospitalized. Currently, little is known about the management and use of packed red blood cell transfusion in hospitalized children with severe IDA. The current Canadian Paediatric Society (CPS) Practice Point on iron requirements in the first 2 years of life (February 2021) provides guidance on prevention of iron deficiency and iron therapy; however, there is no guidance on the use of blood transfusion in children with severe IDA. Choosing Wisely Canada provides guidance on blood transfusions for adults; however, there are no recommendations on transfusion in children. In contrast, the joint American Society of Hematology and American Society of Pediatric Hematology/Oncology Choosing Wisely Task Force recently published (January 2022) recommendations, including avoiding packed red blood cell transfusion for asymptomatic children with IDA and no active bleeding. Objectives: To describe the rate of blood transfusion and characteristics of young children hospitalized with IDA. Design/Methods: Data from children, 6 to 36 months, hospitalized with IDA (2001-2020) was abstracted from health records using a standardized data collection form. Eligibility criteria were discharge diagnosis of IDA according to International Classification of Diseases codes, and laboratory evidence of IDA (hemoglobin < 110 g/L and at least two abnormal markers such as MCV, ferritin, transferrin, iron). Descriptive statistics were used. Results: Of 79 children hospitalized with nutritional IDA (mean age 18.5 months), 34 (43%) received a blood transfusion. Of those receiving a transfusion, the initial mean hemoglobin was 32g/L (range 17-56g/L). Volume of blood given was: 5mL/kg (n=23, 68%), 10mL/kg (n=8, 23%), and >10mL/kg (n=3, 9%). Two children experienced adverse reactions: allergic reaction; non-hemolytic transfusion reaction. Characteristics of the entire cohort (n=79) were: female (n=51, 65%); previously healthy (n=69, 87%); received iron therapy prior to hospitalization (n=6, 8%); tachycardia on presentation (n=47, 59%); daily milk intake (mean 1638mL, range 236-9000mL). Initial laboratory results (mean) were: hemoglobin 40g/L (range 15-85g/L); MCV 51fL; platelet count 574x10 9 /L; ferritin 3ug/L. Management included dietitian consultation with recommendation to reduce milk intake (n=69, 87%) and all patients received oral iron therapy on discharge (n=79, 100%). No child received intravenous iron therapy during their admission. Conclusion: Our findings suggest high rates of blood transfusion among young children hospitalized with iron deficiency anemia. Future research includes examining factors associated with transfusion and practices at other Canadian centres. Our overall aim is to help inform future CPS and Choosing Wisely Canada recommendations.